On Security Threats and Solutions for the Future Smart Home Exploring the Viability of Intrusion Detection in a Centralized Smart Hub - Larsson, Matz; Lipkin, Lisa (My University, 2019)
Security in smart homes is becoming increasingly important as more and more devices are becoming available on the market and the information that they handle is of a sensitive nature. Historical attacks have shown that smart homes can contribute to attacks that could have severe consequences both for their users and for society. While much work is being done on finding security solutions for IoT and smart homes, there has yet to be a consensus on what solutions are optimal. In this thesis we present the state of research in the field and introduce a potential security solution for the smart home. The security solution, called the security supervisor, is a network-based solution located in a smart hub which detects malicious activity within a smart home network. Detection of two attacks are implemented as a proof-of-concept, namely botnet device detection and Evil-Twin attack detection. The results show that the security supervisor is able to detect the former but not the latter, but the authors argue that a similar platform would be able to contribute to increased security and mitigate many threats towards smart homes.
Keywords: Data- och informationsvetenskap; Computer and Information Science